2001
DOI: 10.1042/0264-6021:3560377
|View full text |Cite
|
Sign up to set email alerts
|

The neurofibromatosis 2 protein product merlin selectively binds F-actin but not G-actin, and stabilizes the filaments through a lateral association

Abstract: The neurofibromatosis 2 protein product merlin, named for its relatedness to the ezrin, radixin and moesin (ERM) family of proteins, is a tumour suppressor whose absence results in the occurrence of multiple tumours of the nervous system, particularly schwannomas and meningiomas. Merlin's similarity to ERMs suggests that it might share functions, acting as a link between cytoskeletal components and the cell membrane. The N-terminus of merlin has strong sequence identity to the N-terminal actin-binding region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The COOH terminus of merlin is unique and lacks the conventional actin-binding region of the ERM proteins (merlin interacts with F-actin through its NH 2 terminus). 4,8,10,30,[32][33][34] Several experimental data demonstrated that the merlin overexpression results in a significant decrease in cell proliferation, reversion of Ras-induced transformation, and reduced tumor formation in nude mice. [30][31][32]35,36 The majority of the mutations identified in the NF2 gene results in a truncated protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COOH terminus of merlin is unique and lacks the conventional actin-binding region of the ERM proteins (merlin interacts with F-actin through its NH 2 terminus). 4,8,10,30,[32][33][34] Several experimental data demonstrated that the merlin overexpression results in a significant decrease in cell proliferation, reversion of Ras-induced transformation, and reduced tumor formation in nude mice. [30][31][32]35,36 The majority of the mutations identified in the NF2 gene results in a truncated protein.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,10,30,[32][33][34] Several experimental data demonstrated that the merlin overexpression results in a significant decrease in cell proliferation, reversion of Ras-induced transformation, and reduced tumor formation in nude mice. [30][31][32]35,36 The majority of the mutations identified in the NF2 gene results in a truncated protein. 27,[37][38][39] Conflicting results have been reported with regard to the possible prognostic value of merlin in meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of cellcell adhesion complexes, e.g. catenin-cadherin with actin filaments either directly or through actin-associated proteins, such as a-actinin or members of the ezrin -radixinmoesin protein family have been described (James et al, 2001;Knudsen et al, 1995;Lallemand et al, 2003;Pujuguet et al, 2003;Rimm et al, 1995). Depletion of C. elegans ERM-1 function by RNAi abolishes specifically the assembly of actin microfilaments at the apical cortex of the gut cells.…”
Section: Formation Of the C Elegans Apical Junctionmentioning
confidence: 97%
“…As noted above, merlin lacks the carboxy terminal actin-binding domain that is present in ezrin, radixin and moesin. However, merlin may instead bind actin directly via sequences in its amino terminus [20,79] or indirectly through interactions with other ERM proteins [59,128,137], paxillin [49] or the cytoskeletal protein βII-spectrin [159]. Merlin also binds to and inhibits the action of other proteins directly involved in remodeling of the actin cytoskeleton such as N-WASP [117].…”
Section: Schwannomasmentioning
confidence: 99%